CORONARY HEART DISEASE COMBINED WITH HYPERTENSION - Hubbah Abid; Qobiljonova Shaxnoza Rustam qizi (Modern American Journals, 2025)
The most common cardiovascular diseases —ischemic heart disease, hypertension, and chronic heart failure—are among the most pressing health problems in any society and form the basis of the socially determined diseases identified by the WHO. At the beginning of this century, cardiovascular diseases were the leading cause of death in most economically developed countries. The continuous increase in the number of patients with cardiovascular diseases, their younger age, and significant social consequences (increasing morbidity, disability, and mortality) are leading to increased healthcare costs both in Tashkent and worldwide.